5p14 deletion associated with microcephaly and seizures. Issue 2 (1st February 2000) - Johnson, Elizabeth I; Marinescu, R Catrinel; Punnett, Hope H; Tenenholz, Beverly; Overhauser, Joan
Abstract : We report on a father and son who have an interstitial deletion of 5p14. The father is clinically and mentally normal while the son has significant clinical involvement including microcephaly, seizures, and global developmental delay. The extent of the 5p14 deletion was determined using fluorescence in situ hybridisation (FISH). The deletion in this present family is smaller than a deletion previously described in a multigenerational family that lacks any clinical phenotype. This report shows that a 5p14 deletion does not always lead to a normal phenotype.